Konsep Fasilitas Penunjang Untuk Kawasan Pendidikan - Ade Rafika Yusri; Muhammad Yamin Jinca; Yashinta Kumala Dewi Sutopo (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
The Faculty of Engineering of Hasanuddin University in the Gowa Regency RTRW is an area with an educational function. This study aims to determine the supporting facilities URL inside and outside the Gowa Technical Campus and analyze the supporting facilities needed to support the smooth running of campus activities. Data collection methods used were observation, interviews, questionnaires and literature studies. The analytical method used is a comparative study, Important Performance Analysis (IPA) and gap analysis. The results of this study indicate that the conditions of the supporting facilities URL at the Faculty of Engineering of Hasanuddin University have not been able to meet the needs of students and employees and are still inadequate. Therefore, the concept of providing supporting facilities is arranged based on priority scale, namely, health clinics, lecturer housing, integrated landfills, student centers, hotel conventions, employee housing and bookstores.